Realizing the right to health in Latin America, equitably - Manuela Villar Uribe; Maria-Luisa Escobar; Ana Lorena Ruano; Roberto F. Iunes (BMC, 2021)
Abstract This special issue "Realizing the Right to Health in Latin America and the Caribbean" provides an overview of one of the most challenging objectives of health systems: equity and the realization of the right to health. In particular, it concentrates on the issues associated with such a challenge in countries suffering of deep inequity. The experience in Latin America and the Caribbean demonstrates that the efforts of health systems to achieve Universal Health Coverage are necessary but not sufficient to achieve an equitable realization of the right to health for all. The inequitable realization of all other human rights also determines the realization of the right to health.